Effects of high night temperature on soybean yield and compositions - Yang, Lin; Song, Wenwen; Xu, Cailong; Sapey, Enoch; Jiang, Dong; Wu, Cunxiang (Frontiers in Plant Science, 2023)
Introduction Soybean is sensitive to light and temperature. Under the background of global asymmetric climate warming. Methods The increase of night temperature may have an important impact on soybean yield. In this study, three varieties with different level of protein were planted under 18°C and 28°C night temperatures for investigating the effects of high night temperatures on soybean yield formation and the dynamic changes of non-structural carbohydrates (NSC) during the seed filling period (R5-R7). Results and discussion The results indicated that high night temperatures resulted in smaller seed size, lower seed weight, and a reduced number of effective pods and seeds per plant, and thus, a significant reduction in yield per plant. Analysis of the seed composition variations showed carbohydrates were more substantially affected by high night temperature than protein and oil. We observed “carbon hunger” caused by high night temperature increased photosynthesis and sucrose accumulation in the leaves during the early stage of high night temperature treatment. With elongated treated time, the excessive carbon consumption led to the decrease of sucrose accumulation in soybean seeds. Transcriptome analysis of leaves after 7 days of treatment showed that the expression of most sucrose synthase and sucrose phosphatase genes decreased significantly under the high night temperature. Which could be another important reason for the decrease of sucrose. These findings provided a theoretical basis for enhancing the tolerance of soybean to high night temperature.